2021
DOI: 10.1177/00207640211009266
|View full text |Cite
|
Sign up to set email alerts
|

Home visiting support for people with hikikomori (social withdrawal) provided by experienced and effective workers

Abstract: Objectives: Hikikomori – an almost complete withdrawal from social interaction first seen in Japan – is becoming an emerging psychological syndrome worldwide. The mental health community in Japan has focused on hikikomori since the 1990s. Hikikomori was initially considered a culture-bound trait, unique to Japan; however, it has become an international concern, and cases have been reported even outside of Japan. While home visiting support for people with hikikomori has gained popularity, an effective solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…As noted, however, causality needs to be established, as a reduced level of leaving the house may be an index of other factors, for example a marker of social isolation. A recent intervention for hikikomori in Japan has been to send people into the houses of hikikomori [ 63 ]. Gavin and Brosnan [ 47 ] also found that using social media ameliorated hikikomori risk during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, however, causality needs to be established, as a reduced level of leaving the house may be an index of other factors, for example a marker of social isolation. A recent intervention for hikikomori in Japan has been to send people into the houses of hikikomori [ 63 ]. Gavin and Brosnan [ 47 ] also found that using social media ameliorated hikikomori risk during lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention. Even though few evidence-based interventions have been established, pharmacotherapy (if the individuals are comorbid with psychiatric disorders) [ 3 ], a variety of psychotherapy [ 14 , 47 , 48 ▪ ], social work [ 3 ], and family approach have been provided [ 51 , 52 ▪ , 53 ]. Precision (individualized) approach is recommended based on the above assessments [ 54 , 55 ].…”
Section: The Latest Definition Of Hikikomorimentioning
confidence: 99%
“…Therefore, the threshold for the intervention should be kept as low as possible. In many countries, home visitation programs have been launched to detect, evaluate, and eventually treat socially withdrawn people, which seems to be a logical approach given the nature of the problem (e.g., Japan: Funakoshi et al, 2022 ; Hong Kong: Yuen et al, 2019 ; Korea: Lee et al, 2013 ; Spain: Malagón-Amor et al, 2020 ). Oftentimes (initially) social workers—and not clinical psychologists and psychiatrists—are involved to prevent pathologizing and hence to maximize the chance of a positive acceptation of the help (Li et al, 2018 ).…”
Section: Interventions For Eswmentioning
confidence: 99%